2019
DOI: 10.32725/kont.2019.014
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of Czech patients with diabetic foot ulcers

Abstract: The aim of this study was to assess the quality of life of patients with diabetic foot ulcers, and its dependence on the duration of ulceration, the use of insulin therapy, smoking and Body Mass Index. Design: Cross-sectional study. Methods: A standardized questionnaire, the Diabetic Foot Ulcer Scale, was used for data collection. A quantitative study included 247 adults with diabetic foot ulcers. Data collection was performed between April 2014 and December 2014 in 18 podiatric outpatient and chronic wound ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…Our study showed that the wound's grade and the Diabetic duration are statistically significant and have a relationship related to the quality of life, it was similar to a study conducted in Indonesian (Sari et al, 2018). This study showed that the history of diabetic foot ulcers has no Significant with quality of life Contrary to what was reported in Another study also showed that Patients with a longer history of ulceration had a lower quality of life (Vymětalová and Zeleníková, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Our study showed that the wound's grade and the Diabetic duration are statistically significant and have a relationship related to the quality of life, it was similar to a study conducted in Indonesian (Sari et al, 2018). This study showed that the history of diabetic foot ulcers has no Significant with quality of life Contrary to what was reported in Another study also showed that Patients with a longer history of ulceration had a lower quality of life (Vymětalová and Zeleníková, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Another study found that level of quality of life in patients with diabetes was related to the duration of diabetic foot ulcers -the longer the duration, the lower the quality of life (Vymětalová & Zeleníková, 2019). Considering the present study's findings, it can be said that maintaining foot health improves the quality of life of individuals and ensures the continuity of walking ability, which means that providing training to diabetic patients on diabetes management and foot self-care behaviors can have a positive effect on their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…(Altınok et al, 2016;Trikkalinou et al, 2017). In the relevant literature, the importance of foot care behavior is emphasized in the prevention of the complications of diabetes, especially the diabetic foot, which negatively affects the quality of life (Sothornwit et al, 2018;Vymětalová, & Zeleníková 2019). Khunkaew et al (2019), in their study, identified a relationship between quality of life and foot selfcare, showing that personal foot self-care training, including personal care management practices, helped to improve diabetic patients' quality of life.…”
Section: Introductionmentioning
confidence: 99%